Recruitment variation in subtidal macrofouling assemblages of a Patagonian harbour (Argentina, south-western Atlantic) - Rico, Alicia E. (2010)
The recruitment of subtidal macrofouling organisms was studied in the Patagonian harbour of Comodoro Rivadavia (Argentina, 455135S 672723W). Changes in coverage and density were analysed in the central 100cm2 of upper and lower surfaces which were replaced monthly from January to December 2004. The fouling assemblage consisted of algae, spirorbid polychaetes, compound ascidians, hydrozoans, bryozoans and egg masses spawned by the small fish Helcogrammoides cunninghami. Monthly changes in richness and diversity of taxa on upper and lower surfaces were significantly correlated with sea surface temperature. Fouling assemblage structure differed significantly between upper and lower surfaces. Filamentous algae were dominant on upper surfaces, while filter-feeding invertebrates were more abundant on the lower surfaces of the experimental panels. The density of the spirorbid Romanchella scoresbyi was two orders of magnitude higher on lower than on upper surfaces. Its recruitment began in late winter, reaching maximum values in spring.